Talaromyces marneffei Cu, Zn Superoxide Dismutase Recombinant Protein Expression in Pichia pastoris, Enzymatic Activity and Its Resistance to Oxidative Stress - Khanthawong, Sophit; Wongsawan, Kanruethai; Pratanaphon, Ronachai; Vanittanakom, Nongnuch (Asian Health, Science and Technology Reports, 2024)
Talaromyces marneffei is a dimorphic fungus that is known to cause a disease called talaromycosis, also known as penicilliosis, in immunocompromised individuals. The fungal pathogenicity and virulence factors remain unclear. Superoxide dismutase (SOD) is a neutralizing enzyme through reactive oxygen species generated by the host and has been proven to contribute to the virulence of many pathogenic bacteria and fungi. In this study, full-length sodA gene encoding T. marneffei Cu, Zn SOD was amplified, cloned into pPICzαB vector and successfully integrated into the Pichia pastoris yeast genome. The selected positive clone was induced for protein expression by methanol. An approximately 23 kDa molecular mass of secreted recombinant Cu, Zn SOD is enzymatically active which is like the native and standard enzyme. A rabbit polyclonal antibody raised against recombinant Cu, Zn SOD was proved to be reactive to the native enzyme by using Western blot analysis. pPICzαB/sodA also appeared to be more resistant than the control pPICzαB recombinant yeast in the oxidative stress conditions. This is the first study of the expression of recombinant T. marneffei Cu, Zn SOD protein and its enzyme activity determination. This enzyme is an important virulence factor and targeting this enzyme may be a promising strategy for developing new therapeutics.